Participation of Stakeholders in Corporate Social Responsibility Implementation: A Strategy For Community and Corporate Sustainability (Case Study of Gold Mining Activity in Southeast Sulawesi Indonesia) - Rela, Iskandar Zainuddin; Amin, Fauzan Fakhruddin (Buletin Penelitian Sosial Ekonomi Pertanian Fakultas Pertanian Universitas Haluoleo, 2022)
The sharing and participation of stakeholders from the Government and the community are essential in mining activities. They are concerned with the role of businesses in society's development. A corporate social responsibility (CSR) program aims at enhancing the well-being of the community. This study aims to analyze stakeholder participation in implementing the CSR program. Interviews were conducted on selected respondents based on specific criteria (purposive sampling). Field observations were carried out in the northern Rarowatu sub-district, Bombana Regency in 2015-2019. A total of 30 respondents were selected, consisting of 15 government employees and 15 members of the public. Data were analyzed using the thematic analysis method to determine relevant themes. Findings show three main themes from government feedback in implementing CSR programs: informing from companies, placation, and partnerships. Community activity in the CSR program has only two main themes: information and collaboration. Although Arnstein described eight stages of participation, the present study only describes three levels of participation, where stakeholders are only at the information mediation level. Therefore, this study supports some of the concepts presented by Arnstein. This level of participation suggests that stakeholders are involved in CSR implementation and community development sustainability. In conclusion, the viability of the company's business and good relations with stakeholders comprising the Government and some members of the public should be maintained. They should be fully elaborate in the enterprise's planning, implementation, and evaluation process.